GPC2 antibody–drug conjugate reprograms the neuroblastoma immune milieu to enhance macrophage-driven therapies. Issue 12 (2nd December 2022) - Pascual-Pasto, Guillem; McIntyre, Brendan; Shraim, Rawan; Buongervino, Samantha N; Erbe, Amy K; Zhelev, Doncho V; Sadirova, Shakhnozakhon; Giudice, Anna M; Martinez, Daniel; Garcia-Gerique, Laura; Dimitrov, Dimiter S; Sondel, Paul M; et al.
Abstract : Background: Antibody–drug conjugates (ADCs) that deliver cytotoxic drugs to tumor cells have emerged as an effective and safe anticancer therapy. ADCs may induce immunogenic cell death (ICD) to promote additional endogenous antitumor immune responses. Here, we characterized the immunomodulatory properties of D3-GPC2-PBD, a pyrrolobenzodiazepine (PBD) dimer-bearing ADC that targets glypican 2 (GPC2), a cell surface oncoprotein highly differentially expressed in neuroblastoma. Methods: ADC-mediated induction of ICD was studied in GPC2-expressing murine neuroblastomas in vitro and in vivo. ADC reprogramming of the neuroblastoma tumor microenvironment was profiled by RNA sequencing, cytokine arrays, cytometry by time of flight and flow cytometry. ADC efficacy was tested in combination with macrophage-driven immunoregulators in neuroblastoma syngeneic allografts and human patient-derived xenografts. Results: The D3-GPC2-PBD ADC induced biomarkers of ICD, including neuroblastoma cell membrane translocation of calreticulin and heat shock proteins (HSP70/90) and release of high-mobility group box 1 and ATP. Vaccination of immunocompetent mice with ADC-treated murine neuroblastoma cells promoted T cell-mediated immune responses that protected animals against tumor rechallenge. ADC treatment also reprogrammed the tumor immune microenvironment to a proinflammatory state in these syngeneic neuroblastoma models, with increased tumor trafficking of activated macrophages and T cells. In turn, macrophage or T-cell inhibition impaired ADC efficacy in vivo, which was alternatively enhanced by both CD40 agonist and CD47 antagonist antibodies. In human neuroblastomas, the D3-GPC2-PBD ADC also induced ICD and promoted tumor phagocytosis by macrophages, which was further enhanced when blocking CD47 signaling in vitro and in vivo. Conclusions: We elucidated the immunoregulatory properties of a GPC2-targeted ADC and showed robust efficacy of combination immunotherapies in diverse neuroblastoma preclinical models.